MTPC integration for improved diagnosis of pleural effusion - Zhao, Shuai; Liu, Jiajia; Chen, Jing; Shi, Ji; Ma, Ming; Yan, Haiyang; Sun, Jingna; Geng, Yan (Frontiers in Oncology, 2026)
IntroductionPleural effusion is clinically common with diverse etiologies, and differentiating benign from malignant cases is critical for treatment planning and prognosis assessment. Traditional single diagnostic methods have inherent limitations, leading to diagnostic challenges. This study aimed to develop a multi-modal diagnostic panel (MTPC) to improve the accuracy and efficiency of initial pleural effusion diagnosis.MethodsA total of 369 patients (264 with malignant pleural effusion and 105 with benign pleural effusion) were enrolled retrospectively. The MTPC panel integrated four diagnostic modalities: methylation biomarkers (PTGER4 and SHOX2), tumor markers (CEA and CYFRA21-1), DNA ploidy analysis, and cytological examination. Diagnostic performance was evaluated using sensitivity, specificity, and area under the receiver operating characteristic curve (AUC). Additional analyses were performed for cytology-undetermined and cytology-negative cases.ResultsAmong immunological tumor markers, CEA exhibited the highest specificity (98.1%) and CYFRA21-1 the highest sensitivity (56.8%). Combined PTGER4 and SHOX2 methylation detection achieved a sensitivity of 65.9% and specificity of 92.4%. The MTPC panel demonstrated the best diagnostic performance, with an AUC of 0.8698, sensitivity of 90.2%, and specificity of 83.8%. In cytology-undetermined cases, MTPC reduced “cytology undetermined” reports by 78.4% and missed diagnoses via “negative” reports by 92.3%.DiscussionThe MTPC panel effectively integrates molecular, immunological, chromosomal, and cytomorphological data, significantly improving the diagnostic efficiency of pleural effusion. It addresses the limitations of single diagnostic methods and provides more reliable evidence for clinicians, facilitating early and accurate differentiation of benign and malignant pleural effusions.